2019
DOI: 10.1177/1757975918811102
|View full text |Cite
|
Sign up to set email alerts
|

Building the capacity – examining the impact of evidence-based public health trainings in Europe: a mixed methods approach

Abstract: Objective: Since 2002, a course entitled ‘Evidence-Based Public Health (EBPH): A Course in Noncommunicable Disease (NCD) Prevention’ has been taught annually in Europe as a collaboration between the Prevention Research Center in St Louis and other international organizations. The core purpose of this training is to strengthen the capacity of public health professionals, in order to apply and adapt evidence-based programmes in NCD prevention. The purpose of the present study is to assess the effectiveness of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Based on the results of this study, training topics could include information on accessing the literature and adapting EBIs so that they are relevant to the community. Previous and ongoing studies have demonstrated the benefit of different EBDM training approaches for individuals' confidence and skills related to EBDM [35,[62][63][64][65][66][67]. Within the United States, there are several training programs and materials available to public health practitioners, including those developed by the Regional Public Health Training Centers, the National Network of Public Health Institutes, the Public Health Foundation, CDC, universities, and professional groups such as the National Association of Chronic Disease Directors (e.g., STAR program).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of this study, training topics could include information on accessing the literature and adapting EBIs so that they are relevant to the community. Previous and ongoing studies have demonstrated the benefit of different EBDM training approaches for individuals' confidence and skills related to EBDM [35,[62][63][64][65][66][67]. Within the United States, there are several training programs and materials available to public health practitioners, including those developed by the Regional Public Health Training Centers, the National Network of Public Health Institutes, the Public Health Foundation, CDC, universities, and professional groups such as the National Association of Chronic Disease Directors (e.g., STAR program).…”
Section: Discussionmentioning
confidence: 99%
“…These findings were in accordance with previous reports showing that organizational barriers were more common than personal barriers among public health workers. 16,[24][25][26] In addition, a similar finding by Wahabi et al reported that most students perceived environment and culture as major barriers of EBPH implementation. 19 In contrast, our previous studies demonstrated that physicians and nurses possessed more personal barriers than organizational ones.…”
Section: Discussionmentioning
confidence: 62%
“…14 The best approach for educational training of EBPH is school curriculum for undergraduates. 15 Although many programs for EBPH have been developed worldwide, [16][17][18] efforts on the introduction of curricula for EBPH are little from educational institutions. 19,20 In order to scale up EBPH in the school level, it is imperative to understand the extent to which EBPH is used among the public health department of university.…”
Section: Introductionmentioning
confidence: 99%
“…Our finding that improvements in individual and organizational capacity were minimal, despite increases in workforce development scores and efforts by researchers and practitioners, 23,[34][35][36][37][38][39][40] indicates that continued work is needed to improve evidence-based public health in public health practice at the state level. Innovative or tailored dissemination strategies may be needed to overcome commonly cited barriers to engaging in EBDM, particularly lack of incentives, time, appropriate funding, managerial support, and staff turnover.…”
Section: Discussionmentioning
confidence: 99%